Principales características de la genética bacteriana de Pseudomonas aeruginosa que contribuyen con su patogénesis y resistencia (2013)
ABSTRACT: Pseudomonas aeruginosa has emerged as an important pathogen in the hospital environment due to its role in the origin of diverse clinical conditions and its development of antibiotic resistance. Advances in molecular biology have enabled genome knowledge of this microorganism and elucidated the components that contribute to its pathogenesis and resistance. Objective Describe the main features of core and accessory genomes of P. aeruginosa that promote its pathogenesis and resistance. Methodology Narrative review. Developm ent Genome of P. aeruginosa shows its ability to adapt to different hosts and environments in nature. While the core genome is conserved, the accessory genome is highly variable and is composed of genetic elements as plasmids, transposons and integrons, which do not possess virulence genes only, but also antibiotic resistance genes. Conclusions Pathogenesis and resistance of P. aeruginosa are mediated by diverse genes both constitutive and acquired that promote its persistence in nature and human hosts.